How solitude relates to well‐being in old age: A review of inter‐individual differences. Issue 1 (19th July 2022) - Chen, Yunxiang; Liu, Xiangping
Abstract : Older adults are more likely to live alone and engage in solitary activities than young adults, leading to decrement in their well‐being. However, researchers have discovered beneficial implications of solitude, and some of them even have established that the negative and positive effects of solitude coexist. The study's purposes are to investigate the relationship between solitude and well‐being among older adults and to further examine the inter‐individual differences in this relationship. In the database of Google Scholar, the systematic review methods are used and 17 articles meet the inclusion criteria. The study concludes that older adults experience solitude both negatively and positively; the complex relationship between solitude and well‐being can be better understood and explained by inter‐individual differences based on intrapersonal, interpersonal, and cultural factors. This systematic review adopts a perspective that spans individual and social/cultural levels and helps grasp the link between solitude and well‐being in older adults. Based on this review, the researcher can develop appropriate interventions to help older people maximize the benefits of solitude while minimizing the drawbacks to further achieve a higher quality of life.